Supporting the emotional work of school leaders - Harris, Belinda
This practical book deals with the emotional and moral dimensions of school leadership. The author sets out the intrapersonal and interpersonal attributes, attitudes and behaviours necessary to develop emotional and moral leadership within the school community
Keywords: Educational leadership; Emotional intelligence; School management and organization; Schulleitung; Großbritannien